Which Are the Most Burdensome Functioning Areas in Depression? A Cross-National Study - Kamenov, Kaloyan; Caballero, Francisco Felix; Miret, Marta; Leonardi, Matilde; Sainio, Päivi; Tobiasz-Adamczyk, Beata; Haro, Josep Maria; Chatterji, Somnath; Ayuso-Mateos, José Luis; Cabello, Maria (Frontiers in Psychology, 2016)
Background: The study aimed to identify the most burdensome functioning domains in depression and their differential impact on the quality of life (QoL) of individuals from nine countries in Asia, Africa, Europe, and Latin America. Material and Methods: Data from two multi-country projects—the World Health Organization’s Study on Global Ageing and Adult Health (SAGE) and the Collaborative Research on Ageing in Europe (COURAGE)—were analyzed. Eight functioning domains (pain, mobility, self-care, cognition, interpersonal activities, domestic life and work, sleep and energy, and affect) and QoL were assessed in 4051 individuals with depression. Results: The analyses of the pooled sample showed that affect (ß=-0.21, p<0.001), domestic life and work (ß=-0.16, p<.001) and interpersonal activities (ß=-0.15, p<.001) were the most affected functioning domains. When the analysis was stratified by gender, women showed similar patterns to the total sample, whereas mobility, self-care, cognition and pain were not significant amongst men. The cross-national analysis revealed that difficulties in affect and interpersonal activities were common across countries, whereas the rest of the domains showed country variability. In addition, being a woman (ß=-0.05), being older (ß=0.07), being married (ß=0.05), not having a comorbid condition (ß=-0.03) and having a higher education (ß=0.04) were all factors associated with higher levels of QoL. Conclusions: There was a variation in the level of decrements in different functioning domains across countries. This is in line with the growing evidence that reporting functioning sum-scores obscures potential differences among people. Functioning tools should capture the distinctiveness among individuals in order to provide tailored responses.